Association between rotating night shift work and metabolic syndrome in Korean workers: differences between 8-hour and 12-hour rotating shift work - OH, Jae-Il (Ind Health, 2017)
This study aimed to analyze the association between the shift work schedule and metabolic syndrome (MetS). This is a retrospective longitudinal study based on the 2015 health checkup data of 2,090 workers evaluated for MetS in 2010 at a general hospital in Korea. The participants were divided according to their shift work schedule into daytime, three-shift (8-h rotation), and two-shift (12-h rotation) workers. The index that indicates the association between the shift work schedule and MetS is the odds ratio (OR) calculated using multivariate logistic regression. The analysis for the entire group of workers indicated that there was positive association between two-shift rotation and MetS (OR=1.58, 95% confidence interval [CI]: 1.09, 2.29). In the analysis of rotating night-shift workers, the years of rotating night shifts, frequency of night-shift work, and sleep disturbance were added to the confounding variables, and two-shift work remained positively associated with MetS (OR=1.72, 95% CI: 1.10, 2.70). The risk of MetS differs based on the shift work schedules they engage in. Hence, structural changes to the shift work schedules are required to prevent MetS in night-shift workers.